Dictyocaulosis in cattle: Retrospective analysis of 20 outbreaks in Central Argentina - Ovelar, María Florencia; Canton, German Jose; Odriozola, Ernesto Raul; Lloberas, María Mercedes; Garcia, Juan Agustin (Elsevier, 2024)
Bovine lungworms (Dictyocaulus viviparus) are nematodes which cause a respiratory disease known as verminous bronchitis or pneumonia. In this paper, we describe 20 outbreaks of bovine dictyocaulosis recorded between 2000 and 2023 in Central Argentina. Outbreaks occurred more frequently during the autumn-winter season (from April to August) and affected cattle under 1 year old in beef production systems. An average morbidity and mortality of 26.22 % and 8.44 % were registered, respectively. The main clinical signs observed were respiratory distress (coughing, tachypnea, dyspnea, and nasal discharge), weight loss, weakness, decubitus, and diarrhea. Necropsies were performed in thirty-one calves, heifers, and steers. Gross findings included diffuse interstitial or multifocal pneumonia, with marbled appearance intermingling atelectasis and red-gray firm areas of consolidation, and subpleural and interlobular emphysema and edema. Microscopically, lungs were characterized by abundant edema and mixed intra-alveolar multifocal to coalescent infiltrate. Frequently, adult worms and/or larvae were spotted in the bronchi or alveoli, respectively. Some cases exhibited proliferation of type 2 pneumocytes and hyaline membranes covering the alveolar septa. Co-infections with gastrointestinal nematodes were frequently found in fecal samples. Given the perspective of anthelmintic resistance and future changes in environmental conditions due to climate change, integrated parasitic control strategies are mandatory and should be tailored to each production system. The information gathered in this research provides an overview of lungworm infections in livestock production systems from Central Argentina and could be useful for surveilling, monitoring and designing strategic interventions for the control of this important parasitic disease in the region.